Study on Influence of Different Gamma-ray Energy on Images of an Industrial CT System - Mohamad, Elmy Johana (International Journal of Integrated Engineering, 2018)
Gamma transmission computed tomography is a powerful imaging techniques that provide a cross-sectional view or a volumetric view of the interior of an object. Therefore, reveal structural information of an object as if it had been cut open for viewing. By utilizing the properties of gamma-ray attenuation, images were reconstructed from photon counting data by gamma-ray sensor. Information revealed on these images depends greatly on resolution of the reconstructed images. In this study, the effect of gamma-ray energy used on a portable CT images is studied.Â  Lab sample of four different material densities were used with three different gamma-ray sources namely, Am-241, Ba-133 and Cs-137 to study the effect of energy on the reconstructed images. The best reconstructed image that describes the structure of the sample used in this study is from Ba-133 with energy of 356 keV. The results provide information on suitability of the energy used for the range of material density use in this study.